Pelatihan “Action” untuk Meningkatkan Keterampilan Stimulasi Literasi pada Guru TK - Zahra Santika Utari; Wisjnu Martani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
This study aims at examining the influence of “ACTION” training on improvement of kindergarten teachers’ skills of literacy stimulation. “ACTION” training is training provided for teachers as scaffolder by using activities of sociodrama to improve literacy stimulation skills. The design employed in this study is untreated group control design with dependent pretest and posttest samples. The subjects of the research are 18 kindergarten teachers (9 teachers in the experimental group and 9 teachers in the control group). The research instruments used are the “ACTION” training module, observation guide for literacy stimulation skills, knowledge test of literacy stimulation, and knowledge test sociodrama activity. The statistical test uses the Mann-Whitney U Test. The results of the study show that stimulation literacy skills are significantly higher in the experimental group than in the control group (U = 0,000; p < 0,05). This study concludes that “ACTION” training can improve kindergarten teachers’ skills in literacy stimulation.